Pulsations powered by hydrogen shell burning in white dwarfs - Camisassa, María Eugenia (2016)
Context. In the absence of a third dredge-up episode during the asymptotic giant-branch phase, white dwarf models evolved from low-metallicity progenitors have a thick hydrogen envelope, which makes hydrogen shell burning be the most important energy source. Aims: We investigate the pulsational stability of white dwarf models with thick envelopes to see whether nonradial g-mode pulsations are triggered by hydrogen burning, with the aim of placing constraints on hydrogen shell burning in cool white dwarfs and on a third dredge-up during the asymptotic giant-branch evolution of their progenitor stars. Methods: We construct white-dwarf sequences from low-metallicity progenitors by means of full evolutionary calculations that take into account the entire history of progenitor stars, including the thermally pulsing and the post-asymptotic giant-branch phases, and analyze their pulsation stability by solving the linear, nonadiabatic, nonradial pulsation equations for the models in the range of effective temperatures Teff 15 000-8000 K. Results: We demonstrate that, for white dwarf models with masses M⋆ ≲ 0.71 M⊙ and effective temperatures 8500 ≲ Teff ≲ 11 600 K that evolved from low-metallicity progenitors (Z = 0.0001, 0.0005, and 0.001), the dipole (ℓ = 1) and quadrupole (ℓ = 2) g1-modes are excited mostly as a result of the hydrogen-burning shell through the ɛ-mechanism, in addition to other g-modes driven by either the κ - γ or the convective driving mechanism. However, the ɛ mechanism is insufficient to drive these modes in white dwarfs evolved from solar-metallicity progenitors. Conclusions: We suggest that efforts should be made to observe the dipole g1-mode in white dwarfs associated with low-metallicity environments, such as globular clusters and/or the galactic halo, to place constraints on hydrogen shell burning in cool white dwarfs and the third dredge-up episode during the preceding asymptotic giant-branch phase.